2023
DOI: 10.7759/cureus.40081
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Marginal Fit of Endocrowns Fabricated From Three Different Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM) Ceramic Materials: An In Vitro Study

Abstract: Introduction: The marginal seal and adaptation are important factors for successful restoration. An inadequate marginal seal can lead to bacterial microleakage, plaque accumulation, and eventually treatment failure This in vitro study aimed to compare the marginal gap of endocrowns fabricated from three different computer-aided design/computer-aided manufacturing (CAD/CAM) ceramic materials. Methods: Thirty extracted mandibular molars were selected for the study. Endocrown preparations were complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ]. LDGC and zirconia were the most common all-ceramic materials used for endocrown constructions, with 35% and 30%, respectively, and either alone or in comparisons with other all-ceramic materials.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ]. LDGC and zirconia were the most common all-ceramic materials used for endocrown constructions, with 35% and 30%, respectively, and either alone or in comparisons with other all-ceramic materials.…”
Section: Resultsmentioning
confidence: 99%
“…LDGC and zirconia were the most common all-ceramic materials used for endocrown constructions, with 35% and 30%, respectively, and either alone or in comparisons with other all-ceramic materials. The manual abutment preparation for endocrowns was used in approximately 75% of studies [ 13 16 , 18 , 21 28 ], scanning was used in 90% of studies of endocrown preparation, while the stereomicroscope system was used in 40% of the total studies to record and assess the marginal adaptation in micrometers [ 12 18 ]. The information regarding the involved in vitro studies is presented, along with other characteristics, in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations